Going beyond the state-centrism of critical terrorism studies: studying counterterrorism as contestation across political parties - Gaudino, Ugo (Methodologies in critical terrorism studies, 2024)
Critical Terrorism Studies (CTS) have long argued that security threats are constructed by social and political narratives. Yet, both critical and traditional approaches have frequently privileged the national executives and security agencies as the main units of analysis, assuming that all political parties agree about who represents a security threat for the state. By contrast, this chapter argues that the discourse on terrorism and on the policies to fight it changes across the Right−Left spectrum. The chapter has two aims: first, reflecting on the articulation of the discourse on terrorism beyond the methodological centrality given to the executive power; second, reflecting on case studies that show the politicisation of terrorism by right-wing and left-wing political parties. After defining politicisation as “contestation”, this chapter provides illustrations about Western right-wing leaders and parties who have politicised debates on terrorism by further securitising ethnic minorities and threatening to proscribe anti-fascist organisations and climate activists as extremist subjects. For their part, Western parties on the centre-left have also justified harsh counterterrorism measures in the name of ideological references that differ from conservative ones. The chapter concludes by suggesting that a methodological framework that takes political parties seriously can yield valuable insights for CTS.